Ograniczenia zastosowania metody przepływów między gałęziowych w planowaniu regionalnym - Sangajło, Ryszard (Wydział Prawa i Administracji UAM, 1979)
Stating the needs for improvements in tools of co-ordinative calculus used in the practice of elaboration of short- and medium-term plans of socio-economic development of voivodeships, the author analyses main limits to the utilization of inter-branch method, which is frequently advised in literature. Recognizing insufficiency of empirical elaboration of regional input-output tables in Poland as one of the most important reasons of such state of things the author briefly presents also achievements of two leading countries within this scope, i.e. the U.S.A. and the U.S.S.R. After analysis of a relative insuficiency of such elaborations in Poland the author ascertains that the most important reasons consist in a lack of interest for such elaborations reported by subjects of regional planning and in a very high degree of complexity of obtaining the regional tables of inter-branch flows through collecting statistical data on the way of operational research.
Limitations in Utilization of the Inter-Branch Flows Method in Regional Planning